The HadCM3 contribution to PlioMIP phase 2 - S. J. Hunter; A. M. Haywood; A. M. Dolan; J. C. Tindall (Climate of the Past, 2019)
We present the UK's input into the Pliocene Model Intercomparison Project phase 2 (PlioMIP2) using the Hadley Centre Climate Model version 3 (HadCM3). The 400 ppm CO 2 Pliocene experiment has a mean annual surface air temperature that is 2.9 ∘ C warmer than the pre-industrial and a polar amplification of between 1.7 and 2.2 times the global mean warming. The Pliocene Research Interpretation and Synoptic Mapping (PRISM4) enhanced Pliocene palaeogeography accounts for a warming of 1.4 ∘ C, whilst the CO 2 increase from 280 to 400 ppm leads to a further 1.5 ∘ C of warming. Climate sensitivity is 3.5 ∘ C for the pre-industrial and 2.9 ∘ C for the Pliocene. Precipitation change between the pre-industrial and Pliocene is complex, with geographic and land surface changes primarily modifying the geographical extent of mean annual precipitation. Sea ice fraction and areal extent are reduced during the Pliocene, particularly in the Southern Hemisphere, although they persist through summer in both hemispheres. The Pliocene palaeogeography drives a more intense Pacific and Atlantic meridional overturning circulation (AMOC). This intensification of AMOC is coincident with more widespread deep convection in the North Atlantic. We conclude by examining additional sensitivity experiments and confirm that the choice of total solar insolation (1361 vs. 1365 Wm −2 ) and orbital configuration (modern vs. 3.205 Ma) does not significantly influence the anomaly-type analysis in use by the Pliocene community.